The continued use and disposal of encumbered assets during the Restructuring Directive’s stay - van Hoof, V. J. M. (European Insolvency and Restructuring Journal, 2021)
The Restructuring Directive provides for a temporary stay on individual enforcement actions to support the negotiations on a restructuring plan. The stay should enable the debtor to continue operating or at least preserve the value of their estate during the negotiations. Under normal (going concern) circumstances, the debtor often may use or sell encumbered or third-party owned assets free of security rights in the debtor’s ordinary course of business. If (pre-) insolvency proceedings are opened and a stay applies, the continued use and disposal of encumbered or third-party-owned assets is not always self-evident. During the Directive’s stay, secured creditors cannot enforce their security rights and are at risk of depreciation and value fluctuation of the encumbered assets and the time value cost of delay. A secured creditor may want to terminate the use and disposal if there is uncertainty as to whether he will be (re)paid out of the proceeds or whether their security right passes into the proceeds. The Directive ignores this asset deployment problem, since (1) it does not clarify whether and to what extent powers under the security agreement are affected, and (2) it does not require Member States to protect secured creditors during the stay. The author illustrates how Member States could sensibly deal with the deployment of encumbered assets during the stay by analysing how a stay affects asset deployment in three Member States’ (formal) insolvency procedures aimed at restructuring (Austria, Belgium and the Netherlands), and by drawing inspiration from the UNCITRAL Legislative Guide on Insolvency Law.